Hydrophobic and flexible cellulose aerogel as an efficient, green and reusable oil sorbent1. Issue 100 (29th October 2015) - Lin, Runjun; Li, Ang; Zheng, Tingting; Lu, Lingbin; Cao, Yang
<x xml:space="preserve">Abstract</x> We have developed a low-cost, highly absorbent but degradable, green cellulose aerogel. Furthermore, hydrophobic modification was performed efficiently using cold plasma technology.